Evaluasi Pendampingan dan Strategi Pengembangan UMKM Bimbingan Belajar AHe (Anak Hebat) - Rahmadanti, Nesty Maurilla; Irmalia Canasti; Gabriella Febrina Wanata P; Nur Amalia Wulandari; Nur Haliza Thera A; Siti Nur Lailatus S; Aulia Putri Amanda P; Marshanda Aulia Hendriawan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This activity is a form of implementation of the Small and Medium Business Management (MUKM) course through direct mentoring to a local MSME, Bimbingan Belajar AHe (Anak Hebat). The main goal was to identify and provide appropriate solutions to existing problems so the business can operate more effectively and efficiently. Over approximately three months, we conducted observations, interviews, and analysis of key areas such as marketing, finance, and human resources. Several solutions that could be implemented included designing example Instagram feeds for digital promotion, creating a simple yet organized financial reporting system, and setting Key Performance Indicators (KPIs) for human resources to ensure performance is more measurable. These solutions were tailored to the current condition of the business and were designed to be practical and actionable. We hope that these steps can serve as a foundation for more professional and sustainable business growth in the future.